Designing a Competency-based English Oral Communication Course for Vietnamese Undergraduate Business Administration Students - Tram, Nguyen Thi Minh (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: Vietnam’s accession into international organizations especially ASEAN Economic Community emphasizes the necessity of an appropriate course of English oral communication (EOC) to prepare the business administration (BA) undergraduates with necessary knowledge, skills and abilities to meet the real workplace requirements. The study, therefore, aims at designing an appropriate competency-based EOC course for BA undergraduates. Both quantitative and qualitative data were collected in a mixed methods study. In order to achieve the aims of the study, the course has been designed from the results of a thorough needs analysis starting from interviews with all the stakeholders and then a survey questionnaire with BA undergraduates in a university in Vietnam. Then it was verified with a survey questionnaire with the teachers, piloted with a group of BA undergraduates with observation, questionnaires and reflective journals before being implemented and evaluated with questionnaires, test scores, reflective journals and focus group interview during and after the course, and a questionnaire survey after the internship. The results from both quantitative and qualitative data revealed the effectiveness of the course in improving BA undergraduates’ EOC competencies.